Modern Manufacturing Engineering - Davim, J. Paulo.; Davim, J. Paulo. (Materials Forming, Machining and Tribology, 2015)
This book covers recent research and trends in Manufacturing Engineering. The chapters emphasize different aspects of the transformation from materials to products. It provides the reader with fundamental materials treatments and the integration of processes. Concepts such as green and lean manufacturing are also covered in this book.